Most People Think They Are More Pro-Environmental than Others: A Demonstration of the Better-than-Average Effect in Perceived Pro-Environmental Behavioral Engagement. Issue 1 (2nd January 2020) - Bergquist, Magnus
Abstract: People tend to perceive themselves as better than average in various contexts. In this article I test if the better-than-average effect (BTAE) also holds for pro-environmental behavioral engagement. Experiment 1 supported that the majority of participants report to be more pro-environmental than others, using a large representative sample. Experiment 2 validated these findings in 3 additional cultures (United States, United Kingdom, and India) and showed that BTAE held for both abstract (other Americans) and concrete (my friends) comparisons. Experiment 3 found that participants overestimated both how "much" and how "often" they engage in pro-environmental actions. Finally, Experiment 4 found weak support for the hypothesis that inducing BTAE are inhibiting future pro-environmental behaviors.